Some aspects of Chinese-Australian cooperation in Antarctic research over the past forty years - Chen, Z; Allison, I (Zhongguo Jidi Yanjiusuo,Polar Research Institute of China, 2016)
China and Australia have been collaborating in Antarctic activities since the early 1980s and that collaboration hasgrown and become more formalized as Chinas Antarctic program has expanded. This collaboration has involved personnelexchange, logistic support, environmental protection and particularly scientific research. China and Australia have signed a seriesof memorandums and treaties of friendship and cooperation on Antarctic activities in the past few years. Relevant mechanisms ofcooperation between expedition plans and programs have been established, and the exchange and cooperation in people, scienceand technology, services, and supplies are undertaken across a range of organizations. Here we overview the history of the bilateralcollaboration and provide a few examples of the many areas of cooperation. These examples are focused on activities in Hobart,the key centre of the Australian Antarctic program.